FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERADAAN KOPERASI SISWA DI SMK NEGERI KOTA PEKANBARU - Ilya Dwita Putri; Sumarno Sumarno; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the factors that influence the existence of cooperative students in Pekanbaru State Vocational School, the impact of positive and negative. The informants in this study were student vice-director, quality deputy director, teacher and student. The type of data used in this study is primary and secondary data. Data collection techniques with the help of observation and interviews. Data analysis using descriptive analysis. The results of the study showed that public vocational training in Pekanbaru had 5 cooperative schools and those who did not have 4 schools. The State Vocational Schools that have cooperatives are the reason for cooperative students as a training field for students, cooperative students as learning labs for students and cooperative students who meet all student needs. The State Vocational School that does not have a cooperative is the reason that the human resources in the school do not know what cooperatives are, do not feel the existence of cooperative benefits of students and the lack of student participation. The positive impact of cooperative students is that students and students do not have to leave school to meet their needs, learn students as responsible and independent individuals, cooperative students also teach students to work together. The negative effect is that students are disturbed in time to take care of cooperatives.Key Words: Cooperatives, Student Cooperatives, and Factors Affecting the Exictence